Optimalization of trails tours in Pinge Tourism Village to improve the community's economy during the Covid-19 pandemic - Mahendra, I Wayan Eka; Supartini, Ni Luh; Suwintari, Gusti Ayu Eka; Sulasmini, Ni Made Ayu; Parwati, Komang Shanty Muni (Universitas Muhammadiyah Magelang, 2021)
Pinge Village is the first tourist village in Tabanan Regency which was officially inaugurated by Tabanan Regent Decree No. 337 of 2004 that concerning to Design Pinge Traditional Village as a Tourism Village. This village has several potentials as sources of attractions for tourists. These potentials include beautiful natural scenery, cool air, residential traditional housing, friendly people, and characteristics of rural tourism in the form of